Unrevealing the effect of different dispersion agents on the properties of ethylene–propylene copolymer/halloysite nanocomposites. (5th October 2017) - Bischoff, E.; Gonçalves, G.P.O.; Simon, D.A.; Schrekker, H.S.; Lavorgna, M.; Ambrosio, L.; Liberman, S.A.; Mauler, R.S.
Abstract: The properties of polyolefin nanocomposites strongly depend on the dispersion level of the nanoparticles and the addition of dispersion agents contributes to improving their performance. In this study, the morphology and the mechanical properties of heterophasic ethylene-propylene copolymer/halloysite nanocomposites were tailored by using two hydrogenated hydrocarbon resins: 90% and 100% hydrogenated and two compatibilizing agents: poly(propylene-g-maleic anhydride) and poly(ethylene-octene-g-maleic anhydride). The transmission electron microscopy indicated that the best dispersion of the halloysite nanotubes was achieved when hydrogenated hydrocarbon resins and poly(propylene-g-maleic anhydride) were used simultaneously. All nanocomposites showed an increase in mechanical stiffness and the most pronounced increase of 46% in the Young modulus was achieved with the system containing halloysite, poly(propylene-g-maleic anhydride) and the hydrocarbon resin with the higher degree of hydrogenation. Poly(ethylene-octene-g-maleic anhydride) caused the halloysite nanoparticles to concentrate preferentially in the rubber domains, wherein these hindered the crystallization of polypropylene and polyethylene chains, as showed by atomic force microscopy. In this case, the composite exhibited both high stiffness and improved toughness. These results highlight the key role of dispersion agents in promoting a good balance in the mechanical properties of resulting nanocomposites based on halloysite particles and heterophasic ethylene-propylene copolymers. Graphical abstract: Highlights: Chemical structure of compatibilizing agents affects the HNT placing in the heterophasic matrix. Compatibilizing agents and hydrocarbon resins heavily affect the HNT dispersion/distribution. Hydrocarbon resins improve stiffness of polymer matrix. Dispersion agents promote a selective placing of nanotubes in an heterophasic polymer.